David Tracy's Analogical Imagination in Ethical Action - Little, Brent (Pacifica, 2012)
Although David Tracy's seminal work The Analogical Imagination (1981) primarily addresses the issue of public theology, this study explores the ethical implications of his thought for relationships in the “private” sphere. As Tracy points out, a specifically Christian analogical imagination is an imagination that sees “similarities-indifferences” through the lens of the Christ-event. In regards to interpersonal relationships, then, a Christian analogical imagination, informed by a faith-tradition's religious classics, reflects upon the narrative of Christ in order to discern proper action in an experience with one's neighbour. In addition, Tracy's concept of “manifestation” (here brought into dialogue with Karl Rahner's writings on the unity between love of God and neighbour) allows us to recognise an encounter with the “other” as a possible encounter with grace. By way of conclusion, I discuss a concrete example of the Christian analogical imagination in ethical action: Henri Nouwen's Adam: God's Beloved (1997).